Metajęzyk XML i wbudowane bazy danych w procesie integrowania systemów informatycznych - Niesler, Andrzej (XML and embedded databases in computer systems integration, 2005)
The article is about the usage of embedded databases with native XML support in the process of computer systems integration. It concerns storing, processing, and interchanging semistructural data with an XML representation. The author approaches the problem from the perspective of interoperability in a heterogeneous distributed environment. The main goal of this paper is to discuss the possibilities of using presented technology in integration undertakings.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 74-84